Molybdenum-based nanoparticles (Mo2C, MoP and MoS2) coupled heteroatoms-doped carbon nanosheets for efficient hydrogen evolution reaction - Ren, Jin-Tao; Chen, Lei; Yang, Dan-Dan; Yuan, Zhong-Yong (Applied catalysis. B, Environmental, 2020)
Hierarchically porous hybrid nanosheets with intimately coupled carbon substrate and Mo-based nanoparticles (Mo2C, MoP, and MoS2) are prepared through the universal pyrolysis method without any post-treatments, which exhibit high performance for hydrogen evolution reaction. [Display omitted] •Mo2C, MoP and MoS2 nanoparticles coupled heteroatoms-doped carbon nanosheets for HER.•The synthesized Mo-based materials have significant ultrafine structure and feature.•Excellent electrocatalytic performance for HER in acid and alkaline electrolytes.•Mo-based compounds are the main contribution on the enhanced electrocatalytic activity. Hierarchical nanostructure of intimately coupled transition metal nanoparticles/carbon-based materials can efficiently boost the electrochemical technologies because of the appealingly coupled interaction between different components and the strongly structural advantages. Herein, a facile and conventional strategy is developed to fabricate ultrafine Mo-based nanoparticles (MoP, Mo2C and MoS2) dispersed on hierarchically porous carbon nanosheets. The involved polymer-confinement pyrolysis process can not only efficiently alleviate the aggregation of Mo-based nanoparticles, but also in-situ achieve different Mo-based components on various heteroatoms-doped carbon nanosheets without further post-modification. The hierarchical nanostructure and synergistic effect between carbon substrates and Mo-based nanoparticles enhance the electrochemical performance of the fabricated materials. For instance, the developed MoP@NPCS exhibits outstanding hydrogen evolution performance with high Faradaic efficiency in both acidic and alkaline electrolytes, being one of the impressive catalysts reported to date for hydrogen evolution reaction. This work would inspire the development of interacted carbon-metal functional materials for improving energy-related devices.